2020
DOI: 10.1002/we.2468
|View full text |Cite
|
Sign up to set email alerts
|

A novel sensorless current shaping control approach for SVPWM inverter with voltage disturbance rejection in a dc grid–based wind power generation system

Abstract: A novel sensorless current shaping (CS) control strategy is proposed to avail better power quality (PQ) of a dc grid–based wind power generation system (WPGS) used on a poultry farm by generating an appropriate reference current for space vector pulse width modulation (SVPWM) inverter. The proposed CS strategy also offers adequate control for parallel operation of multiple generators and inverter applications, without requiring voltage and frequency synchronization. Further, to control the poultry farm–based W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Despite the merits of HMG, the coordination and control of hybrid microgrid are becoming a challenging issue. To solve these problems, in References 112,116,117, and 118, different control solutions are provided for HMG operation. In the previously published papers, different control strategies, such as current shaping control, centralized power management approach, hybrid instantaneous theory, and novel restoration technique‐based approaches, are proposed for solving the coordination bidirectional converter problems and improving the stability of HMG operation.…”
Section: Overview Of Different Smg Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the merits of HMG, the coordination and control of hybrid microgrid are becoming a challenging issue. To solve these problems, in References 112,116,117, and 118, different control solutions are provided for HMG operation. In the previously published papers, different control strategies, such as current shaping control, centralized power management approach, hybrid instantaneous theory, and novel restoration technique‐based approaches, are proposed for solving the coordination bidirectional converter problems and improving the stability of HMG operation.…”
Section: Overview Of Different Smg Systemmentioning
confidence: 99%
“…In addition, the proposed approaches are also used for improving the power quality and power reliability of the HMG system during nonlinear/unbalanced load applications. In Reference 116, due to the sensor‐less current shaping control operation, the cost and switching losses significantly decreased to a lesser value and improves the efficiency of the system's performances. In Reference 118, the novel centralized energy management approach (CEMA) offers wireless communication and the CEMA is regulated through the novel control algorithms, such as distributed generation control, battery energy management control, and voltage and frequency control.…”
Section: Overview Of Different Smg Systemmentioning
confidence: 99%
“…In this study, a mechanical model is selected without considering the slip, which is similar to the interaction of the wheel and road in the area known as pseudoslip. 26 The developed model is considered as an ideal model. Moreover, by using the inertia moment of the wheel speed (Ĵ Ω ) and weight of EC, the total inertia moment (J * T ) of each motor can be computed as,…”
Section: Design Of the Behavioral Modelmentioning
confidence: 99%
“…25 TCA is a control approach which prevents the skidding of wheels during slippery road condition. 26 By doing a technical literature survey, it is found that TCA is alternatively termed as an acceleration slip regulation (ASR). 27 To design TCA, different control schemes are suggested by many researchers, and few of them are discussed below.…”
mentioning
confidence: 99%
“…From the literature, it is found that SHAF based on instantaneous PQ theory (IPT), one of the booming solutions for the recognition and mitigation of nonlinear current. However, the performance of the control approach mostly depended on the LPF design, which can be applied with the analog/digital LPF.…”
Section: Introductionmentioning
confidence: 99%